Icacinaceae from the Eocene of western North America. Issue 5 (1st May 2015) - Allen, Sarah E.; Stull, Gregory W.; Manchester, Steven R.
Abstract : Premise of the study: The Icacinaceae are a pantropical family of trees, shrubs, and climbers with an extensive Paleogene fossil record. Our improved understanding of phylogenetic relationships within the family provides an excellent context for investigating new fossil fruit and leaf material from the Eocene of western North America. Methods: We examined fossils from early and middle Eocene sediments of western Wyoming, northeastern Utah, northwestern Colorado, and Oregon and compared them with extant species of Iodes and other icacinaceous genera as well as previously described fossils of the family. Key results: Three new fossil species are described, including two based on endocarps ( Iodes occidentalis sp. nov. and Icacinicaryites lottii sp. nov.) and one based on leaves ( Goweria bluerimensis sp. nov.). The co‐occurrence of I. occidentalis and G. bluerimensis suggests these might represent detached organs of a single species. A new genus, Biceratocarpum, is also established for morphologically distinct fossil fruits of Icacinaceae previously placed in Carpolithus . Biceratocarpum brownii gen. et comb. nov. resembles the London Clay species " Iodes " corniculata in possessing a pair of subapical protrusions. Conclusions: These fossils increase our knowledge of Icacinaceae in the Paleogene of North America and highlight the importance of the Northern Hemisphere in the early diversification of the family. They also document interchange with the Eocene flora of Europe and biogeographic connections with modern floras of Africa and Asia, where Icacinaceae are diverse today. The present‐day restriction of this family to tropical regions offers ecological implications for the Eocene floras in which they occur.